A case report on Beckwith-Wiedemann syndrome with macroglossia - Jefferey Joel; Priya A.; K. Arun Chander (International Journal of Basic & Clinical Pharmacology, 2023)
Beckwith-Wiedemann syndrome (BWS) is a genetic disorder characterized by the overgrowth of various body parts and an increased risk of certain types of cancer. One of the physical features of BWS is macroglossia or an enlarged tongue. In some cases, macroglossia can cause difficulty with speaking, eating, and breathing. A case report on BWS with macroglossia and reduction glossectomy would describe the patient’s symptoms and medical history, as well as the diagnosis, treatment, and outcome of the condition. The patient, a 6 -year-old female, presented with symptoms of macroglossia, which was confirmed by physical examination. The patient also had a history of BWS, which had been diagnosed at birth. The patient’s macroglossia was causing difficulty with speaking and eating regurgitation of food through the nose and was also putting her at risk for sleep apnoea. After a thorough evaluation, the decision was made to perform a reduction glossectomy, which is a surgical procedure that involves removing a portion of the tongue in order to reduce its size. The surgery was performed under general anaesthesia and was successful in reducing the size of the patient’s tongue and improving his ability to speak and eat. The patient recovered well from the surgery and was discharged from the hospital after 3 days of admission. At the 3 months follow-up appointment, the patient had no difficulty with speech, or eating and did not have sleep apnoea. This case report highlights the importance of early diagnosis and treatment of BWS, as well as the potential benefits of reduction glossectomy in managing the symptoms of macroglossia in this condition.